Engaging politics : political participation in Brazil and Sweden, predicted by stereotypes about parliamentarians, political education and behavioral contagion - Carneiro, Thiago Lopes (2015)
Tese (doutorado)—Univerdidade de Brasília, Institute of Psychology, Graduate Program in Social, Work and Organizational Psychology, 2015.